2021
DOI: 10.3390/plants10010081
|View full text |Cite
|
Sign up to set email alerts
|

Identification of F3H, Major Secondary Metabolite-Related Gene That Confers Resistance against Whitebacked Planthopper through QTL Mapping in Rice

Abstract: Whitebacked planthopper (WBPH) is a pest that causes serious damage to rice in Asian countries with a mild climate. WBPH causes severely rice yield losses and grain poor quality each year so needs biological control. Plants resist biotic and abiotic stress using expressing variety genes, such as kinase, phytohormones, transcription factors, and especially secondary metabolites. In this research, quantitative trait locus (QTL) mapping was performed by assigning the WBPH resistance score in the Cheongcheong/Nagd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…If from a biosynthetic point of view F3H is fundamental for the formation of flavan-3-ols, F3’H and F3’5’H are two very important enzymes for the variability of PACs within plants. Indeed, the presence or absence of the gene sequences coding for these two enzymes strongly influence the hydroxylation pattern of B-rings of flavan-3-ols that will constitute the PACs as monomers [ 31 , 32 , 33 ].…”
Section: Biosynthesis Transport and Polymerizationmentioning
confidence: 99%
“…If from a biosynthetic point of view F3H is fundamental for the formation of flavan-3-ols, F3’H and F3’5’H are two very important enzymes for the variability of PACs within plants. Indeed, the presence or absence of the gene sequences coding for these two enzymes strongly influence the hydroxylation pattern of B-rings of flavan-3-ols that will constitute the PACs as monomers [ 31 , 32 , 33 ].…”
Section: Biosynthesis Transport and Polymerizationmentioning
confidence: 99%
“…Besides protective effects during plant growth, anthocyanins may also play important roles in controlling pests and maintaining plant growth. Several recent studies have reported that the increased expression levels of structural anthocyanin genes related with anthocyanin in rice plants are believed to be significant traits for enhancement of rice resistance to the white-backed planthopper [ 151 , 152 ]. A strong positive relationship between anthocyanin concentration and seedling vigor in rice has been also reported [ 153 ].…”
Section: Significant Roles Of Anthocyanin From Purple Rice In Human Healthmentioning
confidence: 99%
“…In this study, we analyzed the developmental behavior of rice tillers using a "Cheongcheong" × "Nagdong" double haploid (CNDH) line. The CNDH lines have been cultivated in a generational process for over 10 years at the Kyungpook National University of Gunwi-gun test field, and it has been used as a bridging parent [18,19]. The aim of this study was to detect the QTL controlling tiller number in the CNDH lines and to explore the dynamics of QTL associations during the whole ontogeny.…”
Section: Introductionmentioning
confidence: 99%